2018
DOI: 10.1111/1365-2664.13270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urbanisation and management practices on pollinators in tropical Africa

Abstract: 1. Urban expansion is an increasing threat to biodiversity, especially in tropical Africa where biodiversity hot spots are being encroached upon by fast-growing cities.Threatened species include bees and other pollinators, which deliver important ecosystem services but are sensitive to land use changes.2. We investigated the impact of urbanisation and vegetation management practices on pollinator abundance, bee diversity, and bee functional traits. We sampled 126 locations in a stratified random design across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Some studies found social species are more frequent in urban habitats surrounded by a high amount of impervious cover compared to suburban or rural sites (Harrison et al 2018;Banaszak-Cibicka et al 2018a;Kratschmer et al 2018). Several studies found no significant urbanization effects on the abundance of eusocial species (Zanette et al 2005;Carper et al 2014;Guenat et al 2019). Urban areas may provide more diverse nesting substrate for social colony building species that can utilize features of the built environment (Cane et al 2006).…”
Section: Socialitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found social species are more frequent in urban habitats surrounded by a high amount of impervious cover compared to suburban or rural sites (Harrison et al 2018;Banaszak-Cibicka et al 2018a;Kratschmer et al 2018). Several studies found no significant urbanization effects on the abundance of eusocial species (Zanette et al 2005;Carper et al 2014;Guenat et al 2019). Urban areas may provide more diverse nesting substrate for social colony building species that can utilize features of the built environment (Cane et al 2006).…”
Section: Socialitymentioning
confidence: 99%
“…A lack of a definition of urbanization or Moretti et al 2017;Brousseau et al 2018) measurement of urbanization is a drawback because environmental effects are not comparable across different studies which hinders generality and synthesis of functional relationships. Furthermore, only a few studies covered the whole gradient from urban to rural sites with a quantification of urbanization (mostly proportion of impervious surface in a buffer around the study site) (e.g., Buchholz et al 2020, Eggenberger et al 2019, Guenat et al 2019. The majority of studies compared sites only along a narrow gradient (e.g., Carper et al 2014, Martins et al 2017, Twerd and Banaszak-Cibicka 2019, sites within one urbanization category (e.g., Pardee and Philpott 2014, Threllfall et al 2015, Quistberg et al 2016, or without properly defining urbanization (e.g., Geslin et al 2016b, Sivakoff et al 2018, Harrison et al 2019).…”
Section: Environmental Data Biasmentioning
confidence: 99%
“…However, while certain studies found a decrease in pollinator richness with increasing urbanization (Hernandez et al 2009, Bates et al 2011, Baldock et al (2015) observed that urban habitat can contain a higher bee richness than farms and protected areas. Likewise, many bees species are associated with open habitats (Klemm 1996), and due to their small body size, they could be benefitted from small habitat fragments (Tscharntke et al 2002, Guenat et al 2019. Thus, species richness, diversity, and composition exhibit contrasting responses to urbanization, and therefore, certain species traits can be good predictors of the impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Urban greenspaces in these two cities, therefore, broadly belong to three different types: (a) amenity land, a greenspace managed for aesthetic or recreational purposes, typically lawns, trimmed hedges, cleared vegetation, or wooded areas; (b) farmed/forested sites, a greenspace managed for agricultural or wood production, including mixed-crop gardens and farms; and (c) informal greenspaces, which are vegetated areas receiving minimal to no management, such as fallows or abandoned sites (cf. Guenat et al, 2019b;Munyati and Drummond, 2020).…”
Section: Study Systemmentioning
confidence: 99%